Determinants of intrapreneurial intention of small tea exporters in Sri Lanka - Wijetunge, Wijetunge Arachchige Deepani Sajeewa; Yusoff, Siti Khalidah Binti Md; Azam, Ferdous; Tham, Jacquline (International Journal of Management and Sustainability, 2024)
The purpose of the study is to investigate the factors affecting the intrepreneurial intentions of small tea exporters in Sri Lanka. Intentions are crucial in any behavior to realize such behaviors and yield expected results. Owing to the problem of this study as how to initiate innovations in the global tea market, the study was carried out to find out the determinants of intentions of small tea exporters in Sri Lanka. This is a quantitative study followed by deductive reasoning. This study selected small tea exporters with the view of enhancing their intentions to proceed with these innovations, as large tea exporters are already introducing innovations to the tea industry. The study collected data from 120 small tea exporters who had registered with the Sri Lanka Tea Board by the end of 2020 using a structured questionnaire. The findings revealed that Individual Entrepreneurial Orientation (IEO), attitudes, and Entrepreneurial Self-efficacy (ESE) have significant and positive impact on Intrapreneurial Intention (INI) of small tea exporters in Sri Lanka while IEO contributes more to the INI. Finally, the findings of this study provide useful insights for small tea exporters in stimulating their intentions towards the introduction of innovations leading to a better performance in the global tea market. Further, it will guide policymakers and the government in designing the appropriate policies, rules, and regulations in this context.